Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† Ø§Ù„Ø¨ÙŠØ¦Ø© Ù…Ø¹ ÙØ¹Ø§Ù„ÙŠØ© Ø§Ù„Ù…ØØ§Ø¯Ø«Ø© Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Ro'fat Hizmatul himmah; Muhammad Alvian (Institut Agama Islam Darusssalam Blokagung, 2021)
This study aims to identify the increase in low speaking skills among students who live in Arabic language dormitories in Blokagung Banyuwangi, so that they can speak Arabic in that language. This research is a research which is a field research which is located in a language dormitory, and the methods used in obtaining data are observation, documentation and questionnaires, while the data analysis uses the steps by collecting data on the students who live in Arabic language dormitories. Research results: Students get a lot of speaking practice with the subjects offered by the teacher because the priority of applying this direct method is to improve students' ability to speak Arabic